2015
DOI: 10.1016/j.matdes.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gate design and cavity thickness on filling, morphology and mechanical properties of microinjection mouldings

Abstract: Miniaturized parts weighing single or tens of milligrams represent a large category of microinjection moulded products. Both miniaturization and extreme processing under microinjection moulding subject material to high shear rates and high cooling rates, and cause the same material to have different morphologies and final properties when used in conventional injection moulding. It also makes mold design challenging. This study investigates the effects of micro gate design (opening and thickness) and cavity thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The properties of PP/CNT nanocomposite were not available in the materials database for Moldflow. In this scenario, a substitution could be chosen from the software database to perform simulation analysis . Then, a replacement of unfilled PP (Adstif HA740N, Basell Polyolefins North America), which has a similar structure to that of the PP used in this study, was selected for evaluating the distribution of possible maximum shear rates within microparts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The properties of PP/CNT nanocomposite were not available in the materials database for Moldflow. In this scenario, a substitution could be chosen from the software database to perform simulation analysis . Then, a replacement of unfilled PP (Adstif HA740N, Basell Polyolefins North America), which has a similar structure to that of the PP used in this study, was selected for evaluating the distribution of possible maximum shear rates within microparts.…”
Section: Methodsmentioning
confidence: 99%
“…Then, a replacement of unfilled PP (Adstif HA740N, Basell Polyolefins North America), which has a similar structure to that of the PP used in this study, was selected for evaluating the distribution of possible maximum shear rates within microparts. The actual processing conditions were extracted from injection molding machine and were employed as the inputs to Moldflow to represent the actual molding conditions .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The slight discrepancy could be attributed to the presence of higher shear rates in the microinjection molding (µIM) process, which largely favors the orientation of CNT in the flow direction. The difference of skin/core ratio could be another contributing factor as Zhang et al . found that there is a remarkable increase of skin/core ratio with a decrease of part thickness in µIM.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the materials experience high stresses and shear rates. This thermomechanical situation could have an influence on the nucleation and growth rate of crystalline entities as far as to material degradation .…”
Section: Introductionmentioning
confidence: 99%